2016
DOI: 10.1051/0004-6361/201527511
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the outer bulge with RRab stars from the VVV Survey

Abstract: Context. The VISTA Variables in the Vía Láctea (VVV) is a near-IR time-domain survey of the Galactic bulge and southern plane. One of the main goals of this survey is to reveal the 3D structure of the Milky Way through their variable stars. In particular, enormous numbers of RR Lyrae stars have been discovered in the inner regions of the bulge (−8• ) by optical surveys such as OGLE and MACHO, but leaving an unexplored window of more than ∼47 sq deg (−10.0• and −10.3• b −8.0 • ) observed by the VVV Survey. Aims… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
79
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(87 citation statements)
references
References 51 publications
(89 reference statements)
8
79
0
Order By: Relevance
“…The distance distributions of the RR Lyrae in our sample compared with 1019 RR Lyrae type ab recently discovered in the outer bulge from the VVV survey (Gran et al 2016) have consistent peak values. The distribution of the present sample is very concentrated, much more so than the observed distribution of RR Lyrae in the inner and outer bulge.…”
Section: Distancessupporting
confidence: 78%
See 1 more Smart Citation
“…The distance distributions of the RR Lyrae in our sample compared with 1019 RR Lyrae type ab recently discovered in the outer bulge from the VVV survey (Gran et al 2016) have consistent peak values. The distribution of the present sample is very concentrated, much more so than the observed distribution of RR Lyrae in the inner and outer bulge.…”
Section: Distancessupporting
confidence: 78%
“…VVV near-infrared color-magnitude diagram for the Galactic center region showing the position of the nuclear bulge RR Lyrae (black stars). For comparison, the unreddened outer bulge RR Lyrae Gran et al (2016) are shown to the left of the color-magnitude diagram (white dots). The direction of the reddening vector is also shown.…”
Section: Metallicitiesmentioning
confidence: 99%
“…Its spatial distribution seems to be uncorrelated with the bar position, appearing as an extended, centrally concentrated and possibly spheroidal component. This is supported by the distribution found for other tracers of metalpoor old populations such as RR Lyrae stars (Pietrukowicz et al 2012;Dékány et al 2013;Kunder et al 2016;Gran et al 2016; but see also Pietrukowicz et al 2015). On the chemical abundance side, α-abundance ratios with respect to iron are systematically enhanced over its whole metallicity range.…”
Section: Introductionsupporting
confidence: 58%
“…Moreover, from the observed mass-metallicity relation for galactic spheroids (Gallazzi et al 2005), a system with mean metallicity around [Fe/H] = −0.4 dex, as our metal-poor component is, should have a mass of ∼10 10 M , which is comparable to the total bulge mass as estimated from observations (Valenti et al 2016). Furthermore, RR Lyrae stars, as tracers of metal-poor old stellar populations, have been shown to display an axisymmetric spatial distribution, uncorrelated with the bar position angle (Dékány et al 2013;Gran et al 2016), and a high-velocity dispersion of around 130 km s −1 (Gratton 1987;Kunder et al 2016). However, this is still under debate; a recent analysis of OGLE data suggests that the RR Lyrae distribution might be elongated with a pivot angle comparable to that of the main bar (Pietrukowicz et al 2015).…”
Section: Discussionmentioning
confidence: 52%
“…Dékány et al 2013, Gran et al 2016. We have found hundreds of RRab stars located in a thin strip across the Galactic disk (Minniti et al 2017), at Galactic latitudes −2.24 < b < −1.05 deg, and Galactic longitudes (295 < l < 350 deg).…”
Section: Introductionmentioning
confidence: 96%